Circular RNAs: Biomarkers of cancer. Issue 3 (21st September 2022) - Cui, Jingyi; Chen, Meng; Zhang, Lanxin; Huang, Sida; Xiao, Fei; Zou, Lihui
Abstract: Circular RNAs (circRNAs) are a class of single‐stranded closed RNAs that are produced by the back splicing of precursor mRNAs. The formation of circRNAs mainly involves intron‐pairing‐driven circularization, RNA‐binding protein (RBP)‐driven circularization, and lariat‐driven circularization. The vast majority of circRNAs are found in the cytoplasm, and some intron‐containing circRNAs are localized in the nucleus. CircRNAs have been found to function as microRNA (miRNA) sponges, interact with RBPs and translate proteins, and play an important regulatory role in the development and progression of cancer. CircRNAs exhibit tissue‐ and developmental stage–specific expression and are stable, with longer half‐lives than linear RNAs. CircRNAs have great potential as biomarkers for cancer diagnosis and prognosis, which is highlighted by their detectability in tissues, especially in fluid biopsy samples such as plasma, saliva, and urine. Here, we review the current studies on the properties and functions of circRNAs and their clinical application value. Abstract : This study demonstrates that circular RNAs (circRNAs) have great potential as biomarkers for cancer diagnosis and prognosis, which is highlighted by their detectability in tissues and fluid biopsy samples. CircRNAs may act as biomarkers in cancers including glioma, bladder cancer, breast cancer, gastric cancer, hepatocellular carcinoma, colorectal cancer, lung cancer, kidney cancer, pancreatic cancer, and leukemia.